Research, Literacy, and Communication Education: New Challenges Facing Disinformation - Puebla-Martínez, Belén; Gallardo-Camacho, Jorge; Marta-Lazo, Carmen; Romero-Rodríguez, Luis Miguel (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The information that comes through digital media and social networks is increasing. This potential access to almost infinite information makes it difficult to select relevant content with a good understanding. It is therefore necessary to generate research that thoroughly analyses the phenomenon of communication and information in the digital age. For this reason, this monograph presents different research studies that highlight the need for greater media literacy and education in order to prevent the existence and dissemination of fake news. Citizens must know how to deal with disinformation and be able to detect the source of bad intentions behind information. Therefore, people need to be aware of the new communication challenges in order to determine what is important, which media they can trust, and where information has been misused or manipulated. In conclusion, society must be prepared to face new challenges related to misinformation. An educated and digitally literate society will be able to face these problems and be prepared to face the new communication challenges, including interaction with social networks, new audiences, new media, fake news, etc.